2016
DOI: 10.1002/adma.201670027
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Electronics: A Stretchable Electronic Fabric Artificial Skin with Pressure‐, Lateral Strain‐, and Flexion‐Sensitive Properties (Adv. Mater. 4/2016)

Abstract: A new type of wearable electronic fabric based on helical‐ and coaxial‐structure designs is fabricated for artificial skin application by S.‐H. Yu and co‐workers, as described on page 722. The combination of the helical and coaxial structures endows the fabric with high stretchability. This electronic fabric, with only one kind of sensor unit, can simultaneously map and quantify the mechanical stresses induced by normal pressure, lateral strain, and flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Stretchable strain sensors have attracted extensive attentions due to their potential applications in a variety of fields such as flexible electronics, soft robotics, , and health monitoring. In recent years, massive efforts have been devoted to develop flexible strain sensor with combined superiority of flexibility, broad sensing range, high sensitivity, and mechanical stability of the strain sensor. To date, it is still a great challenge to fabricate strain sensors with simultaneous large workable strain range and high repeatability. Low detection limit, which is one of the key indicators of a strain sensor, as well as the maximum detection strain is equally important in expanding the workable strain range.…”
Section: Introductionmentioning
confidence: 99%
“…Stretchable strain sensors have attracted extensive attentions due to their potential applications in a variety of fields such as flexible electronics, soft robotics, , and health monitoring. In recent years, massive efforts have been devoted to develop flexible strain sensor with combined superiority of flexibility, broad sensing range, high sensitivity, and mechanical stability of the strain sensor. To date, it is still a great challenge to fabricate strain sensors with simultaneous large workable strain range and high repeatability. Low detection limit, which is one of the key indicators of a strain sensor, as well as the maximum detection strain is equally important in expanding the workable strain range.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these considerable achievements in stress and strain sensors, the construction of a stretchable multimode mechanical sensor capable of sensing pressure, strain, and flexion for monitoring human body motions ranging from subtle deformations to substantial movements remains a challenge. , Ge et al reported an electronic fabric with the ability of simultaneously mapping and quantifying mechanical stresses induced by pressure, lateral strain, and flexion. The fabric was based on intertwined sensor electrodes with piezoresistive rubber as the shell sensing element and silver-nanowire-coated elastic thread as the stretchable and highly conductive core electrode …”
Section: Introductionmentioning
confidence: 99%
“…The rapid and substantial progress in the development of different stretchable electronics has recently stimulated strong research interest. Examples include wearables, [1][2] artificial skin, [3][4] stretchable displays, [5][6] and so on. In particular, mechanically deformable energy-harvesting [7][8] and energy-storage [9][10][11] devices are crucial for achieving efficacy and portability.…”
Section: Introductionmentioning
confidence: 99%